PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP HASIL BELAJAR PADA MATA PELAJARAN GEOGRAFI DI SMAN 2 BUKITTINGGI - Di, Renal; khairani, Khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
Today, science and technology have an impact on the world of education. Teachers are required to use an effective model by using technology. One model that applies technology in teaching is the flipped classroom model. This study aims to determine the effect of the flipped classroom learning model on geography learning outcomes at SMAN 2 Bukittinggi. By using the experimental method in the form of a quasi-experimental model. The research subjects were class X.IPS 4 as the experimental class and class X.IPS 1 as the control class. The sampling technique used was Random Sampling. The data in the study were in the form of a test of student learning outcomes for class X. Social studies. With data collection techniques in the form of interviews, using learning outcomes tests, namely Pretest and Posttest and documentation. Data processing uses individual completeness, normality test, homogeneity test along with T test to determine the hypothesis. The results in this study there is an increase in learning outcomes between the experimental class and the control class. Based on the average calculation, the experimental class got 82.21 results, the control class got 68.43 results. Based on the effectiveness analysis using the Gain Value, the experimental class effectiveness value was 67%, and the flipped classroom model was quite effective to be applied, while for the control class, the effectiveness value was 46%, the conventional model was less effective to apply.